2019
DOI: 10.1021/acs.inorgchem.8b03446
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Reactive Fe(III) Clusters by Freeze-Dry/Solvent-Exchange To Benchmark Iron Hydrolysis Pathways

Abstract: Isolating Fe­(III) clusters from water without stabilizing ligands is significantly challenged by the high acidity of Fe3+-bound water, leading to uncontrolled precipitation of iron oxyhydroxides. Here we demonstrate a freeze-drying solvent-exchange method that enabled the isolation of a metastable Fe­(III) sulfate decameric cluster formulated [Fe10O2(SO4)12­(OCH3)2]·14CH3OH (Fe 10 ). Without stabilization by solvent-exchange, the aqueous species undergoes rapid conversion to the iron sulfate mineral schwertm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to the CCDC database up to March 2022, there are only three cases of inorganic structures containing sulfate groups coordinated to aluminum. They are S-Al32 reported by Sun et al, 31 Al(III) substituted iron sulfate clusters reported by Nyman et al, 32 and SO 4 functionalized MOF-520 reported by Yaghi et al 33 In these structures, SO 4…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to the CCDC database up to March 2022, there are only three cases of inorganic structures containing sulfate groups coordinated to aluminum. They are S-Al32 reported by Sun et al, 31 Al(III) substituted iron sulfate clusters reported by Nyman et al, 32 and SO 4 functionalized MOF-520 reported by Yaghi et al 33 In these structures, SO 4…”
Section: Introductionmentioning
confidence: 78%
“…According to the CCDC database up to March 2022, there are only three cases of inorganic structures containing sulfate groups coordinated to aluminum. They are S-Al32 reported by Sun et al, Al­(III) substituted iron sulfate clusters reported by Nyman et al, and SO 4 functionalized MOF-520 reported by Yaghi et al In these structures, SO 4 2– acts as appendants on Al­(III), and its role as a linker has not been explored. Our particular interest in aluminum­(III) coordination chemistry has resulted in a broad range of new structure types including high nuclearity hydrotalcite-like aluminum oxo clusters and aluminum molecular rings. To expand applications of aluminum­(III)-based compounds in the field of chirality, we are interested in synthesizing chiral crystalline materials constructed from inorganic achiral SO 4 2– components.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The molecular and electronic structures of metastable species of POMs are only substantiated by nuclear magnetic resonance, mass spectrometry, small-angle X-ray scattering and other spectroscopy techniques. [8,9] Thanks to the adjustable compositions of POMs and their high negative charges with numerous bare oxygen coordination sites, POM-templated silver nanocluster chemistry has gained remarkable progresses. [10] Different sizes, charges, and geometries of POMs can lead to diverse silver shells, which in turn act as molecular containers to trap some active POM intermediates followed by structural determinations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the enormous polyoxometallates (POMs) such as Keggin, Dawson and Lindqvist structures have been determined by single crystal X‐ray diffraction (SCXRD), the atom‐precise structures of kinetically controlled intermediate species remain a black box by virtue of their fast dynamic hydrolysis‐condensation reaction in solution [8] . The molecular and electronic structures of metastable species of POMs are only substantiated by nuclear magnetic resonance, mass spectrometry, small‐angle X‐ray scattering and other spectroscopy techniques [8,9] . Thanks to the adjustable compositions of POMs and their high negative charges with numerous bare oxygen coordination sites, POM‐templated silver nanocluster chemistry has gained remarkable progresses [10] .…”
Section: Introductionmentioning
confidence: 99%